Analysis of Gold Pawn Product Trends at BPRS Sarana Prima Mandiri Bangkalan in 2021–2024 - Latipah, Latipah; Setiawan, Firman (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the dynamics of gold pawn product trends at BPRS Sarana Prima Mandiri Bangkalan during the 2021–2024 period. Gold pawning is an attractive option for the public due to its practicality, security, and compliance with Islamic principles. However, fluctuations in the number of customers highlight the need for a trend analysis to identify emerging patterns. This research adopts a descriptive quantitative approach using secondary data from the annual reports of BPRS Sarana Prima Mandiri. The data were analyzed through percentage change calculations and presented in tables and graphs. The findings reveal a decline in customers from 1,165 in 2021 to 1,093 in 2022. A sharp drop occurred in 2023 with only 199 customers, followed by a slight recovery to 314 in 2024. Overall, the gold pawn product trend declined steeply between 2021 and 2023, with indications of minor recovery in 2024. These results emphasize the need for innovative strategies to sustain and enhance customer interest.